Modèles d’organisation thématique des paragraphes et entre les paragraphes, à l’épreuve de la Rectorique de Cyceron - Guy Achard-Bayle; Ondřej Pešek (Discours)
The article addresses the issue of the topical organisation of the paragraph and between paragraphs. It is divided into two parts: in the first part, we approach the issue through two theoretical models, one French and the other Czech. In the second part of the article, the models are tested on a corpus study. The study applies a two-pronged approach: the first, historical, consists in analysing the marks of segmentation as they were used in a medieval manuscript, playing the role of “precursors” of markers of the paragraph; the second, contemporary, focuses on the modern edition of the same text. By projecting the thematic and compositional structure on the division of the text into paragraphs, we illustrate the role these segments play as text-organising devices.